New species of Central American Rhopalothrix Mayr, 1870 (Hymenoptera, Formicidae) - Longino, John T.; Boudinot, Brendon E. (Zootaxa, 2013)
The ant genus Rhopalothrix is a rare inhabitant of wet forest leaf litter and soil. We propose a monophyletic R. isthmica clade that is restricted to the Neotropics, contains most of the species in the genus, and has its center of abundance and diversity in Central America. Thirteen species are recognized in the R. isthmica clade, of which eight are described as new and three are redescribed. A key to species in the R. isthmica clade is provided, and the following eight new species are described: R. andersoni Longino & Boudinot, sp. nov., R. apertor Longino & Boudinot, sp. nov., R. atitlanica Longino & Boudinot, sp. nov., R. megisthmica Longino & Boudinot, sp. nov., R. nubilosa Longino & Boudinot, sp. nov., R. sub-spatulata Longino & Boudinot, sp. nov., R. therion Longino & Boudinot, sp. nov., and R. triumphalis Longino & Boud-inot, sp. nov.. Queens are newly associated with workers for three Central American species. New synonymy is proposed for Rhopalothrix plaumanni Brown & Kempf, 1960 = R. acutipilis Kempf, 1962, syn. nov.